AB0572 Meta-analysis of the key rheumatoid arthritis (RA) disease activity endpoints in patients treated with B-cell depleting therapies. (23rd January 2014) - Menon, S.; Barker, K.; Peeva, E.; Gourley, I.; Heatherington, A.
Abstract : Background: Two recent meta-analyses are available in the literature (Lee et al., 2010 and Volkmann et al., 2010). In this meta-analysis we included additional recently published studies (nine in all) and analyzed all the RA disease activity endpoints at week 24 focusing on both anti-TNF naïve and experienced patients. Objectives: To compare and evaluate RA disease activity endpoints in several similar published studies in the last decade in order to examine the effect of B cell depleting therapy on RA disease activity. Methods: Unlike the other meta-analysis that exclusively uses logit method, this analysis used the method of Mantel-Hansel (MH) for the analysis of the ACR20, 50 and 70. The MH method was chosen for the current analysis due to its relative simplicity and its wide use in the medical literature. For DAS28, the effect sizes were combined using the inverse variance as the weighting factor so that studies with larger sample sizes were given more weight than smaller studies. In addition, we looked at the disease activity at week 24 for all studies. Results: The estimated effect was comparable in all studies at week 24 although the treatment effect is slightly lower in IMAGE study. The confidence intervals for the Ocrelizumab (ACTION) and Rituximab (EDWARDS) studies were wider due to the relative smaller sample size. The trends were similar for anti-TNF naïve and experienced patients. Similar observations were made for ACR50, ACR70 and DAS28. Conclusions: This meta-analysis indicates that in recent trials with B-cell depleting therapy, the therapies have a large and highly reproducible effect on RA disease activity which is not affected by prior receipt of anti-TNF therapy. Disclosure of Interest: None Declared